EFEKTIVITAS PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYALAHGUNAAN BBM BERSUBSIDI JENIS SOLAR YANG BERDAMPAK PADA PENAMBANG EMAS TANPA IZIN DI WILAYAH POLRES KUANTAN SINGINGI - Abdul Rahman; Yudi Krismen (STKIP Subang, 2026)
The misuse of subsidized diesel fuel is a criminal offense that not only causes financial losses to the state but is also closely linked to the rampant illegal gold mining activities occurring in Kuantan Singingi Regency. The availability of subsidized diesel fuel supports the operation of the dredging machines used by illegal miners; therefore, law enforcement against these two crimes should be conducted synergistically. This study aims to analyze the effectiveness of law enforcement by the Kuantan Singingi Police against the criminal misuse of subsidized diesel fuel and its impact on illegal gold mining activities in the region. The research method employed is a normative legal approach using legislative and conceptual frameworks. The findings indicate that law enforcement against the misuse of subsidized diesel has not been effective due to limited resources, weak inter-agency coordination, and a lack of commitment among law enforcement officials. These conditions directly contribute to the continued operation of unlicensed gold mining, which is increasingly widespread. Comprehensive and coordinated legal enforcement system reform is needed to break the chain linking these two interconnected crimes.